Expanding Australian indigenous entrepreneurship education ecosystems - Alex Maritz; Dennis Foley (Administrative Sciences, 2018)
Australian Indigenous entrepreneurship and entrepreneurship education represents a significant opportunity for Indigenous people to enhance their entrepreneurial skills, in turn building vibrant Indigenous-led economies that support sustainable economic development and social well-being. This study is the first of its kind to explore the conceptualization of a framework of Australian Indigenous entrepreneurship education ecosystems. The purpose is to provide emergent inquiry and participatory action research into entrepreneurship education ecosystems, enabling the expansion of Indigenous research and practice; with the objective of delineating specific fundamentals associated with Indigenous entrepreneurs, such as limitations in social, human, and financial capital. We include and integrate Australian Indigenous value perspectives, including Indigenous knowledge, wisdom, and resilience, as well as the cultural captivity of entrepreneurship and Indigenous culture. The addition to the body of knowledge provides practical implications and a framework to the benefit of all ecosystem participants, including entrepreneurship educators, Indigenous entrepreneurs, policy-makers, training suppliers, and dynamic institutional participants, such as incubators, accelerators, and community development initiatives.
Keywords: 350; Australian Indigenous entrepreneurship; entrepreneurship education; entrepreneurship education ecosystems